THE EFFECT OF AUDIT FEE , AUDIT TENURE AND PUBLIC ACCOUNTING FIRM (KAP) SIZE ON AUDIT QUALITY (STUDY ON BANKING COMPANIES LISTED ON THE BEI, 2020-2022) - Aini, Ratna Nurul; Krisnawati, Hani; Andini, Rita (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
This research aims to determine the influence of audit fees , audit tenure and KAP size on audit quality in banking sector companies listed on the Indonesia Stock Exchange in 2020-2022. This type of research is quantitative using secondary data originating from the company's annual report. The population of this research was 47 banking companies. And the sample in this study was 29 companies selected using side purposive techniques . The data analysis technique in this research uses logistic regression analysis with the SPSS 24 program. The results of this research show that audit fees have a positive and significant effect on audit quality, while audit tenure and KAP size have no effect on audit quality in banking sector companies listed on the BEI period. 2020-2022